Interesting case of allergic broncho pulmonary aspergillosis (ABPA) with high-attenuation mucus (HAM). Issue 5 (24th May 2021) - Bhatt, Ritisha; Ghosh, Soumitra; Handa, Neha; Tale, Sudheer
Abstract : A 25-year-old man, who was taking treatment for his poorly controlled asthma, presented with symptoms of cough with expectoration, gradually progressive shortness of breath, fever on and off and diffuse wheeze for 2 years. Chest X-ray revealed hyperinflation of lung field with dense opacification at right upper lobe. High-resolution CT chest showed bilateral patchy consolidation, central bronchiectasis and high-attenuation mucus (HAM) impaction. His blood absolute eosinophil count, total serum IgE level, Aspergillus fumigatus specific IgE and IgG level were 1910, 16760 kU/L, 59.8 kU/L and 147.41 kU/L, respectively. Diagnosis of allergic broncho pulmonary aspergillosis (ABPA) was established according to International Society for Human and Animal Mycology society guidelines. He was started on systemic steroids and doing well after 6 months of follow-up. Our case illustrates HAM, which is a rare but typical radiological feature of ABPA.